Economic attractivity of foreign direct investments in CEMAC zone : harmonization of the legal instruments to the international rules - (:unkn) unknown (My University, 2015)
The currents of the globalization of the markets, marked by the free movement of capital and the phenomenon of free trade supported the implementation of Community policies of economic revival and attractivity of the territories. It is in this impetus that geographical regroupings with economic aiming like the Economic community and Monetarist of Central Africa (CEMAC) appeared. Six countries of Central Africa of which Cameroon, Congo, Gabon, Equatorial Guinea, the Central African Republic and Chad are members and are for it, the object our analysis on the economic attractivity of direct foreign investment (FDI) in this under-area. The FDI became an inevitable actor of the development process, and CEMAC zones, a privileged destination for the investors. It appears nevertheless an ambiguity in the relationship between the flow of FDI, the economic growth and the development of the member countries of the CEMAC : the rate unceasingly crescent of flows of FDI entering the under-area, is unfortunately not always synonymous with economic growth. To understand this paradox, one carries out an analysis of the instruments framing of the IDE under-area CEMAC. This reveals that, for an optimal output of these devices and the warranty of one long-term economic growth in these States, it is necessary to associate the current policies of economic attractivity of the FDI, with a diversification of the exploitable economic domains, but also to adapt the international standards to sociocultural but so economic specificities of under-area CEMAC. The case of the countries of the BRICS can in this respect, being used as illustration for an “other way” of thinking the development.
Keywords: African Research